A construção da participação democrática na província da Catalunha (Espanha) e no Brasil: clivagens e consensos - Toledo, Rodrigo Alberto [UNESP] (My University, 2012)
The article searches to launch some analyses and investigations on the historical reach of produced participative processes in Spain and Brazil. Evidently, both the processes if had uncurled in historical, social, economic contexts and distinct politicians, but, exactly thus, keep some approaches that we intend to give prominence in the present article. For example, the popular mobilization in the two presented cases after occurred a long period of not attendance of social demands socials. In the same way, the processes of democratic renewal of both are related with historical landmarks “end of the cold war” and the dismantlement of the State of well-being that introduced new rationalists in the relation between governing and governed dynamic, over all in the coinage and offer of public politics. How much to the dismantlement of the State of social welfare, we present, still, that in the case of Spain occurred a decentralization of its formulator power to decide arrangement of public politics that started to count on the participation of social actors in the called relational city (BECERRA, 2011). In the case of Brazil, the dictatorial period (1964-1985), the fast urban growth and the generation of precarious peripheries in the main cities, the distension and the Constituent (1986-1988) had generated the enough forces of pressure so that, gradually, if it incorporated the participative arrangement in the power to decide process. We identify that in both the cases, kept the had ratios, the instauration of a critical scene of suppression/absence of formulated public politics from an interface with the social movements were the propeller spring of the transformations in the power to decide mechanisms of formularization and implementation of public politics.

O artigo busca lançar algumas análises e indagações sobre o alcance histórico de processos participativos engendrados na Espanha e no Brasil durante as décadas de 1980 e 1990. Evidentemente, ambos os processos se desenrolaram em contextos históricos, sociais, econômicos e políticos distintos, mas, mesmo assim, guardam algumas aproximações às quais pretendemos dar destaque no presente artigo. A mobilização popular, nos dois casos apresentados, ocorreu após um longo período de supressão/não atendimento de demandas sociais. Da mesma forma, os processos de renovação democrática de ambos estão relacionados com os marcos históricos “fim da guerra fria” e o desmantelamento do Estado de bem-estar, que introduziu novas dinâmicas racionalistas na relação entre governantes e governados, sobretudo na cunhagem e na oferta de políticas públicas. Quanto ao desmantelamento do Estado de bem-estar social, apresentamos ainda que, no caso da Espanha, provocou reflexos no modus operandi do processo de formulação e implementação de políticas públicas. Ocorreu, em outras palavras, uma descentralização de seu arranjo decisório formulador de políticas públicas, que passou a contar com a participação de atores sociais no denominado município relacional (BECERRA, 2011). No caso do Brasil, o período ditatorial (1964-1985), o rápido crescimento urbano e a geração de periferias precárias nas principais cidades, a distensão e a Constituinte (1986-1988) geraram as forças de pressão suficientes para que, paulatinamente, incorporassem-se os arranjos participativos no processo decisório. Identificamos que, em ambos os casos, guardadas as proporções, a instauração de um cenário crítico de supressão/ausência de políticas públicas formuladas a partir de uma interface com os movimentos sociais foi a mola propulsora das transformações nos mecanismos decisórios de formulação e implementação de políticas públicas.
Keywords: Participative democracy; Public politics; Power to decide process; State of social welfare; Brazil and Spain; Democracia participativa; Políticas públicas; Processo decisório; Estado de bem-estar social; Brasil e Espanha